2015
DOI: 10.1093/schbul/sbv101
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Address Medical Conditions and Health-Risk Behaviors Among Persons With Serious Mental Illness: A Comprehensive Review

Abstract: People with serious mental illness (SMI) have mortality rates 2 to 3 times higher than the overall US population, largely due to cardiovascular disease. The prevalence of cardiovascular risk factors such as obesity and diabetes mellitus and other conditions, such as HIV/AIDS, is heightened in this group. Based on the recommendations of a National Institute of Mental Health stakeholder meeting, we conducted a comprehensive review examining the strength of the evidence surrounding interventions to address major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 186 publications
2
123
1
Order By: Relevance
“…9 However, there are few practical and effective treatment models for people with SMI that target self-management of mental and medical disorders concurrently. 10,11 A recent literature review of studies that specifically focused on medical conditions and risk behaviors among persons with SMI found that the strength of evidence was low for most interventions. 10 While multiple studies have described self-management programs for DM and SMI individually, 1219 few have addressed self-management of DM and SMI concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, there are few practical and effective treatment models for people with SMI that target self-management of mental and medical disorders concurrently. 10,11 A recent literature review of studies that specifically focused on medical conditions and risk behaviors among persons with SMI found that the strength of evidence was low for most interventions. 10 While multiple studies have described self-management programs for DM and SMI individually, 1219 few have addressed self-management of DM and SMI concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…Individualized support has been shown to be beneficial for people with SMI as it increases the frequency and duration of interventions [30] and helps address motivational and cognitive issues associated with the numerous challenges this population faces. Peer specialists, whose duties typically include a "linkage to services" function [9], are especially well-positioned to offer increased individualized support to intervention participants, as this type of support is already part of their role in managing clients' engagement with services and other service providers.…”
Section: Discussionmentioning
confidence: 99%
“…However, we dispute the statement that lifestyle interventions show little evidence of reducing cardiovascular risk, especially since such interventions are broadly as effective as pharmacological interventions 2 . The evidence shows that appropriately-designed behavioural interventions that provide sufficient support to patients to increase their autonomy significantly reduce cardiometabolic risk factors in the short to medium term , 3 . If maintained over the long-term, we can expect physical health outcomes and life expectancy to improve, as is well-documented in the general population 4 .…”
Section: Word Count: 392mentioning
confidence: 99%